Mechanism of optimization of investment activity in the system of integration technologies of maritime transport (Economics and region, 2022)
World trade law is based on two global sectors. One covers the entire freight space, the other is concentrated within regional sectors of the freight market limited by factors. At the same time, the formation of the world freight market is influenced by international economic relations and the relationship between the demand for international trade transportation and the carrying capacity of the fleet in certain specialized sectors of the transport services market. Merchant shipping has an international global character. It should be considered a regularity that the functioning of the major economies of the international economy is closely linked to merchant shipping. In addition, sea freight and cruise traffic are characterized by active dynamics, which affects the development of shipbuilding, metallurgy and ship power systems. Strengthening of the international division of labor defines the tasks of integration and innovation activities in the maritime transport services market. Due to the lack of cash surpluses and financially constrained states, as well as under the influence of crisis situations, investment resources are withdrawn from the maritime transport industry of countries such as Ukraine and provide redistribution of cargo flows between the merchant fleet of other maritime countries. When choosing a strategy and policy for the development of the national maritime transport complex, it is necessary to take into account the most important factors of international trade that determine the parameters of the world market of transport services. The world maritime transport system is developing, despite periods of crisis, at a faster pace than other modes of transport and industrial production, which determines the international division of labor. Therefore, the assessment of dynamic processes in the world maritime trade market is necessary to characterize the impact of international economic relations on the parameters of the development of cargo flows, fleet and ports.
Keywords: integration technologies; maritime transport; strategy; freight market; optimization